Il viaggio a Reims [dramma giocoso in one act] - Rossini, Gioachino 1792-1868 (Opus Arte, 2007)
A diverse group of European nobility and gentry are making their way to Reims for the coronation of French King Charles X. They are stuck in a spa, called the Golden Lily. They are unable to make the last leg of the trip because there are no horses and carriages to be hired. They turn their virtual imprisonment there into a house party, with plenty of opportunity for romantic intrigues and self-made entertainment